Penerapan Model Pembelajaran Quantum Teaching Prinsip TANDUR Terhadap Peningkatan Kemampuan Komunikasi Matematis - Ninik Setiasih; Uba Umbara; M. Irfan Habibi (JUMLAHKU: Jurnal Matematika Ilmiah STKIP Muhammadiyah Kuningan, 2016)
Quantum Teaching with TANDUR principle is a learning model that apply six stages ,while learning to grow , natural , frontage , demonstrate , repeat , andcelebrate. This study aims to 1) compare the skill of mathematical communication students using model quantum teaching with TANDUR principle with students who use direct instructional model, 2) to increase the skill of mathematical communication students who obtain mathematical learning using a model quantum teaching with TANDUR principle, 3) evaluate the response students towards learning model quantum teaching with TANDUR principle.The method used in this study is a quasiexperimental method by taking a sample of eighth grade students as the experimental class C and F as the control class VIII SMPN 2 Kuningan. From the results of the post-test show that the mean of the control groups score are 44,77 then the mean of the experimental classes score is 51,50. The data that getting from post-test doesn’t come from the normal distribution. So, this data was compared by using MannWhitney (U) test. From the analyze, we know that